Powder metallurgy friction material, method for manufacturing the same, brake pad, and hydroelectric generator
Patent Information
- Application Number
- CN202511128309.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-12
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-08-12
AI Technical Summary
传统铜基材料在高速制动时,摩擦界面温度可达800℃以上,导致铜基体软化,增强相(如碳化硅)与基体结合力下降,出现颗粒脱落,粉尘量高达45mg/次
[0041] Compared to existing technologies, the powder metallurgy friction material provided in this application can reduce the amount of dust generated during braking by more than 60% by adjusting the content of each component and the particle size distribution in the raw materials.
Smart Images

Figure CN120961911B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of powder metallurgy friction materials technology, and in particular to a powder metallurgy friction material and its preparation method, brake pads, and a hydro-generator. Background Technology
[0002] Most existing medium and large-sized hydro-generator units employ a pneumatic jacking system located beneath the rotor for mechanical braking. This system utilizes non-metallic, asbestos-free friction materials, which experience significant wear. During braking, this not only generates substantial amounts of dust but may also produce irritating gases. Powder metallurgy friction materials are widely used in high-speed braking applications, and their performance directly impacts braking efficiency and safety. Traditional copper-based materials experience friction interface temperatures exceeding 800℃ during high-speed braking, leading to softening of the copper matrix, decreased bonding strength between the reinforcing phase (such as silicon carbide) and the matrix, and particle shedding, resulting in dust levels as high as 45mg / cycle. Because hydro-generators using hydraulic disc brakes house the brakes within the confined space of the unit's top cover, the dust from these powder metallurgy friction materials is difficult to manage. Dust contamination of the slip rings can degrade their insulation performance, creating safety hazards. Summary of the Invention
[0003] This application provides a powder metallurgy friction material and its preparation method, a brake pad, and a hydro-generator, which reduces the amount of dust generated during braking by the powder metallurgy friction material, thereby at least partially solving the above-mentioned technical problems.
[0004] To achieve the above objectives, according to a first aspect of this application, a powder metallurgy friction material is provided, which is obtained by sintering the following raw materials, wherein the raw materials comprise, by mass percentage:
[0005] The copper powder is 50 wt% to 60 wt%, and the average particle size of the copper powder is 48 μm to 105 μm.
[0006] Iron powder 10wt%~15wt%;
[0007] Graphite 8wt%~12wt%;
[0008] Molybdenum disulfide 4wt%~6wt%;
[0009] The tantalum carbide comprises 3 wt% to 5 wt%, wherein the average particle size of the tantalum carbide is in the nanometer range;
[0010] Zirconium dioxide 3wt% to 5wt%, wherein the average particle size of the zirconium dioxide is in the nanometer range;
[0011] Aluminum powder 2wt%–4wt%; and
[0012] Polyethylene glycol 1wt% to 3wt%.
[0013] Optionally, the copper powder includes at least one of electrolytic copper powder and atomized copper powder.
[0014] Optionally, the iron powder includes foamed iron powder.
[0015] Optionally, the average particle size of the iron powder is 5 μm to 10 μm.
[0016] Optionally, the graphite is in the form of flakes.
[0017] Optionally, the average particle size of the graphite is 10 μm to 50 μm.
[0018] Optionally, the molybdenum disulfide has an average particle size of 1 μm to 3 μm.
[0019] Optionally, the average particle size of the tantalum carbide is less than or equal to 100 nm.
[0020] Optionally, the average particle size of the aluminum powder is in the micrometer range.
[0021] Optionally, the relative molecular mass of the polyethylene glycol is 1000 to 1200.
[0022] Optionally, the density of the powder metallurgy friction material is greater than or equal to 5.2 g / cm³. 3 .
[0023] Optionally, the porosity of the powder metallurgy friction material is less than or equal to 8%.
[0024] According to a second aspect of this application, a method for preparing a powder metallurgy friction material is provided, comprising:
[0025] Provide materials other than polyethylene glycol in the raw materials, and mix them to obtain a premix;
[0026] Ethanol and polyethylene glycol are added to the premix, and the mixture is ball-milled to obtain a slurry; in the slurry, the mass ratio of the premix to the ethanol is 1:(0.5-0.6), and the mass ratio of the premix to the polyethylene glycol is 1:(0.15-0.2);
[0027] The slurry is spray-dried to obtain a powder, wherein the content of polyethylene glycol in the powder is 1 wt% to 3 wt%.
[0028] The powder is prepared into a blank;
[0029] The blank is sintered to obtain the powder metallurgy friction material.
[0030] Optionally, the slurry further includes N-β-hydroxyethyl ethylenediamine triacetic acid, and the mass ratio of the premix to the N-β-hydroxyethyl ethylenediamine triacetic acid is 1:(0.003-0.005).
[0031] Optionally, the particle size of the powder is 100μm to 220μm.
[0032] Optionally, 40 wt% of the powder particles have a particle size of 200 μm to 220 μm, 30 wt% of the powder particles have a particle size of 140 μm to 160 μm, and 30 wt% of the powder particles have a particle size of 100 μm to 120 μm.
[0033] Optionally, the preparation method of the powder metallurgy friction material further includes vacuum drying the premix.
[0034] Optionally, in the slurry obtained by ball milling, the average particle size of the solid particles is less than or equal to 20 μm.
[0035] Optionally, the powder is prepared into a blank by cold pressing, with a cold pressing pressure of 25MPa to 30MPa and a holding time of 5s to 10s.
[0036] Optionally, the sintering process is performed in a hydrogen atmosphere.
[0037] Optionally, the sintering temperature of the sintering treatment is 900℃~950℃, and the holding time is 1.5h~2.5h.
[0038] According to a third aspect of this application, a brake pad is provided, comprising a friction body, wherein the friction body comprises the powder metallurgy friction material described above or the powder metallurgy friction material prepared by the method described above.
[0039] Optionally, the hardness of the brake pads is greater than 35HB.
[0040] According to a fourth aspect of this application, a hydro-generator is also provided, including the aforementioned brake pads.
[0041] Compared to existing technologies, the powder metallurgy friction material provided in this application can reduce the amount of dust generated during braking by more than 60% by adjusting the content of each component and the particle size distribution in the raw materials.
[0042] Other features and advantages of this application will be described in detail in the following detailed description section. Attached Figure Description
[0043] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0044] Figure 1 This is a three-dimensional structural schematic diagram of the brake pads provided in some embodiments of this application.
[0045] Explanation of reference numerals in the attached figures:
[0046] 1. Brake pads. Detailed Implementation
[0047] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. In addition, it should be understood that the specific implementation methods described herein are only for illustration and explanation of this application and are not intended to limit this application.
[0048] In this application, unless otherwise stated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of the device in its actual use or operating state; while "inner" and "outer" refer to the outline of the device. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative purposes and do not impose numerical requirements or establish an order.
[0049] In this application, "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.
[0050] In this application, "at least one" means one or more, and "more than one" means two or more. "One or more", "at least one of the following", or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0051] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.
[0052] According to a first aspect of this application, an embodiment of this application provides a powder metallurgy friction material, which is obtained by sintering the following raw materials; by mass percentage, the raw materials include: 50wt%–60wt% copper powder, 10wt%–15wt% iron powder, 8wt%–12wt% graphite, 4wt%–6wt% molybdenum disulfide, 3wt%–5wt% tantalum carbide, 3wt%–5wt% zirconium dioxide, 2wt%–4wt% aluminum powder, and 1wt%–3wt% polyethylene glycol. The average particle size of the copper powder is 48μm–105μm; the average particle size of the tantalum carbide is in the nanometer range; and the average particle size of the zirconium dioxide is in the nanometer range.
[0053] In the aforementioned raw materials, copper powder serves as the base metal, accounting for a relatively high proportion, typically half or more of the total raw material mass. Based on the total mass of the raw materials, the copper powder content is within the range of any one or any two of the following: 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, 56wt%, 57wt%, 58wt%, 59wt%, and 60wt%. Copper powder provides excellent thermal conductivity to powder metallurgy friction materials, effectively transferring the heat generated during friction and thus reducing thermal damage and wear. Specifically, the copper powder is coarse copper powder with an average particle size of 48μm to 105μm. As an example, the average particle size of the copper powder is a range of any one or any two of 48 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, and 105 μm. Optionally, the copper powder includes at least one of electrolytic copper powder and atomized copper powder. Electrolytic copper powder has higher purity and a larger specific surface area, which makes it perform well in terms of pressing and forming properties. Atomized copper powder has a lower bulk density, which allows it to better improve the compactness and mechanical properties of the product.
[0054] Iron powder is another matrix metal. The addition of iron powder enables powder metallurgy friction materials to have higher hardness and strength. However, the content of iron powder in the raw material is usually lower than that of copper powder, and excessive iron powder content may affect the stability of the friction coefficient of the powder metallurgy friction material. Based on the total mass of the raw material, the iron powder content is any one or a range between 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, and 15 wt%. Optionally, the iron powder includes foamed iron powder. The friction coefficient of foamed iron powder has relatively smaller fluctuations, which is beneficial for maintaining the stability of the friction coefficient of the powder metallurgy friction material. In addition, compared with copper powder, the average particle size of iron powder is smaller. Optionally, the average particle size of iron powder is 5 μm to 10 μm. As an example, the average particle size of iron powder is any one or a range between 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm.
[0055] Graphite and molybdenum disulfide are used as lubricating components. Both graphite and molybdenum disulfide have a layered structure, which allows them to form a continuous lubricating film with low shear stress during friction, thereby reducing the coefficient of friction and wear. The ratio of graphite to molybdenum disulfide in the raw materials is typically controlled so that they can work synergistically to improve the lubrication performance of the material. Based on the total mass of the raw materials, the graphite content is any one or a range between 8 wt%, 8.5 wt%, 9 wt%, 9.5 wt%, 10 wt%, 10.5 wt%, 11 wt%, 11.5 wt%, and 12 wt%, and the molybdenum disulfide content is any one or a range between 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, and 6 wt%. Optionally, the graphite is flake-shaped. The interlayer interaction of the flake-shaped graphite through weak van der Waals forces gives it good lubricity. However, graphite and molybdenum disulfide are prone to poor dispersibility during the preparation of powder metallurgy friction materials. Optionally, the average particle size of graphite is 10 μm to 50 μm, and the average particle size of molybdenum disulfide is 1 μm to 3 μm, which can promote the dispersion of graphite and molybdenum disulfide in the matrix metal. As an example, the average particle size of graphite is any one or any two of 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, and 50 μm, and the average particle size of molybdenum disulfide is any one or any two of 1 μm, 1.5 μm, 2 μm, 2.5 μm, and 3 μm.
[0056] Tantalum carbide and zirconium dioxide are used as friction components. Both tantalum carbide and zirconium dioxide possess high melting points and good high-temperature chemical stability, which enables them to exhibit excellent tribological properties under different rotational speeds and temperatures. In the raw materials, the mass content of tantalum carbide is any one or a range between 3wt%, 3.5wt%, 4wt%, 4.5wt%, and 5wt%, and the mass content of zirconium dioxide is any one or a range between 3wt%, 3.5wt%, 4wt%, 4.5wt%, and 5wt%. The average particle size of both tantalum carbide and zirconium dioxide is nanometer-sized, which strengthens the bonding force between tantalum carbide and zirconium dioxide and the matrix, reducing particle shedding at the friction interface. In particular, the combination of nanometer-sized tantalum carbide and zirconium dioxide with coarse-grained copper powder can effectively improve the interfacial bonding strength. Optionally, the average particle size of tantalum carbide is less than or equal to 100 nm, and the average particle size of zirconium dioxide is less than or equal to 100 nm. As an example, the average particle size of tantalum carbide is 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, and the average particle size of zirconium dioxide is 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm.
[0057] Aluminum powder acts as a fluxing agent, preferentially melting during the sintering process to promote eutectic formation, reduce the porosity of the resulting powder metallurgy friction material, increase its density to greater than 90% of the theoretical density, and reduce wear paths. The mass content of aluminum powder in the raw material is any one of 2wt%, 2.5wt%, 3wt%, 3.5wt%, and 4wt%, or a range between any two. Optionally, the average particle size of the aluminum powder is in the micrometer range.
[0058] Polyethylene glycol is used as a binder. The aluminum powder content in the raw material is any one of 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, and 3 wt%, or a range between any two. Optionally, the relative molecular mass of the polyethylene glycol is 1000–1200.
[0059] Compared to existing technologies, the powder metallurgy friction material provided in this application can reduce the amount of dust generated during braking by more than 60% by adjusting the content of each component and the particle size distribution in the raw materials.
[0060] In some embodiments, the density of the powder metallurgy friction material is greater than or equal to 5.2 g / cm³. 3 The porosity of powder metallurgy friction materials is less than or equal to 8%.
[0061] According to a second aspect of this application, a method for preparing a powder metallurgy friction material is also provided. This method is used to prepare the aforementioned powder metallurgy friction material. The method for preparing the powder metallurgy friction material includes:
[0062] S1. Provide the materials other than polyethylene glycol from the above raw materials and mix them to obtain a premix;
[0063] S2. Add ethanol and polyethylene glycol to the premix and ball mill to mix them to obtain a slurry; in the slurry, the mass ratio of premix to ethanol is 1:(0.5~0.6), and the mass ratio of premix to polyethylene glycol is 1:(0.15~0.2);
[0064] S3. Spray dry the slurry to obtain powder, the content of polyethylene glycol in the powder is 1wt% to 3wt%;
[0065] S4. Prepare the powder into a blank;
[0066] S5. The blank is sintered to obtain powder metallurgy friction material.
[0067] In some embodiments, the slurry further includes N-β-hydroxyethylethylenediaminetriacetic acid (N-β-hydroxyethylethylenediaminetriacetic acid), with a mass ratio of premix to N-β-hydroxyethylethylenediaminetriacetic acid of 1:(0.003–0.005). Adding N-β-hydroxyethylethylenediaminetriacetic acid during ball milling inhibits metal oxidation and reduces porosity defects; N-β-hydroxyethylethylenediaminetriacetic acid acts as a chelating agent, binding to hydroxyl groups on the metal surface, blocking oxygen adsorption, and reducing the ball milling oxidation rate. As an example, the mass ratio of premix to N-β-hydroxyethylethylenediaminetriacetic acid is 1:0.003, 1:0.0035, 1:0.004, 1:0.0045, or 1:0.005.
[0068] In some embodiments, the particle size of the powder is 100 μm to 220 μm. The slurry is spray-dried to form small particles. The pseudo-particles formed by spray drying of the slurry have good sphericity, which facilitates molding. The organic solvent ethanol evaporates during the spray granulation process, leaving only 1 wt% to 3 wt% polyethylene glycol, which helps the small particles agglomerate and acts as a binder.
[0069] In some embodiments, 40 wt% of the powder particles have a particle size of 200 μm to 220 μm, 30 wt% of the powder particles have a particle size of 140 μm to 160 μm, and 30 wt% of the powder particles have a particle size of 100 μm to 120 μm. By using multi-sized particle size powders, the pressing density can be increased, thereby improving the wear resistance.
[0070] In some embodiments, the preparation method of powder metallurgy friction materials further includes vacuum drying the premix. As an example, the premix is placed in a vacuum drying oven for dehydration at 120°C for 2 hours.
[0071] In some embodiments, the average particle size of the solid particles in the slurry obtained by ball milling is less than or equal to 20 μm. Ball milling reduces the particle size of the raw materials, ensures uniform mixing of components, and partially alloys them.
[0072] In some embodiments, the powder is cold-pressed into a blank at a pressure of 25 MPa to 30 MPa and a holding time of 5 to 10 s. The powder is filled into a mold and cold-pressed to obtain the blank. As an example, the cold-pressing pressure is any one or a range between 25 MPa, 26 MPa, 27 MPa, 28 MPa, 29 MPa, and 30 MPa, and the holding time is any one or a range between 5 s, 6 s, 7 s, 8 s, 9 s, and 10 s.
[0073] In some embodiments, the sintering process is carried out in a hydrogen atmosphere.
[0074] In some embodiments, the sintering temperature is 900°C to 950°C, and the holding time is 1.5h to 2.5h. As an example, the sintering temperature is any one or a range between 900°C, 910°C, 920°C, 930°C, 940°C, and 950°C, and the holding time is any one or a range between 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, and 2.5h.
[0075] By employing multi-stage particle size blending and low-temperature sintering processes, the density of the resulting powder metallurgy friction material can be greater than or equal to 5.2 g / cm³. 3 And the porosity is less than or equal to 8%.
[0076] According to the third aspect of this application, please see Figure 1 This application also provides a brake pad 1, which includes a friction body, the friction body including the powder metallurgy friction material described above or the powder metallurgy friction material prepared by the above-mentioned powder metallurgy friction material preparation method.
[0077] In some implementations, the hardness of the brake pad 1 is greater than 35HB.
[0078] According to a fourth aspect of this application, a hydro-generator is also provided, including the aforementioned brake pad 1.
[0079] To address the drawback of existing friction materials producing excessive braking dust, which makes them unsuitable for use in hydro-generator braking, this application provides a powder metallurgy friction material with low braking dust. By fabricating this powder metallurgy friction material into brake pads 1 and applying them to hydro-generators, the amount of dust generated during braking can be effectively reduced, thereby reducing the risk of dust contaminating the slip rings of the hydro-generator and improving the safety of the hydro-generator during operation.
[0080] The following description is based on specific embodiments.
[0081] Example 1
[0082] This embodiment provides a powder metallurgy friction material, which is obtained by sintering the raw materials shown in Table 1:
[0083] Table 1
[0084] Copper powder 60 90μm Iron powder 12 9μm graphite 10 20μm Molybdenum disulfide 5 2μm Tantalum carbide 4 30nm Zirconium dioxide 4 30nm aluminum powder 3 8μm polyethylene glycol 2 /
[0085] The preparation process of this powder metallurgy friction material includes:
[0086] S1. Pretreatment: The materials in Table 1, except for polyethylene glycol, are premixed and then dehydrated in a vacuum drying oven (120℃, 2h) to obtain the premix.
[0087] S2. Mixing and ball milling: Add the premix to a ball mill along with ethanol (55% of the premix mass), polyethylene glycol (15% of the premix mass, relative molecular weight: 1100) and N-β-hydroxyethylethylenediaminetriacetic acid (0.5% of the premix mass) and ball mill until the particle size is ≤20μm to obtain a slurry.
[0088] S3. Spray drying: The slurry is spray-dried to obtain powder. The particle size of the powder is controlled to be 100μm~220μm (of which 210±10μm accounts for 40wt%, 150±10μm accounts for 30wt%, and 110±10μm accounts for 30wt%), while the mass content of polyethylene glycol in the powder is controlled to be 2wt%.
[0089] S4. Pressing and sintering: The powder is filled into a mold and cold-pressed (cold pressing pressure is 25MPa, holding time is 5s), and then sintered under hydrogen protection (sintering temperature is 950℃, holding time is 2h) to obtain powder metallurgy friction material.
[0090] Example 2
[0091] This embodiment provides a powder metallurgy friction material, which is obtained by sintering the raw materials shown in Table 2:
[0092] Table 2
[0093] Copper powder 59 90μm Iron powder 10 9μm graphite 12 20μm Molybdenum disulfide 6 2μm Tantalum carbide 3 30nm Zirconium dioxide 5 30nm aluminum powder 2 8μm polyethylene glycol 3 /
[0094] Please refer to Example 1 for the preparation process of this powder metallurgy friction material. The difference is that the raw materials are different and the mass content of polyethylene glycol in the powder in S3 is 3 wt%.
[0095] Example 3
[0096] This embodiment provides a powder metallurgy friction material, which is obtained by sintering the raw materials shown in Table 3:
[0097] Table 3
[0098] Copper powder 60 90μm Iron powder 15 9μm graphite 8 20μm Molybdenum disulfide 4 2μm Tantalum carbide 5 30nm Zirconium dioxide 3 30nm aluminum powder 4 8μm polyethylene glycol 1 /
[0099] Please refer to Example 1 for the preparation process of this powder metallurgy friction material. The difference is that the raw materials are different and the mass content of polyethylene glycol in the powder in S3 is 1 wt%.
[0100] Example 4
[0101] This embodiment provides a powder metallurgy friction material, which is obtained by sintering the raw materials shown in Table 4:
[0102] Table 4
[0103] Copper powder 50 90μm Iron powder 15 9μm graphite 12 20μm Molybdenum disulfide 6 2μm Tantalum carbide 5 30nm Zirconium dioxide 5 30nm aluminum powder 4 8μm polyethylene glycol 3 /
[0104] Please refer to Example 1 for the preparation process of this powder metallurgy friction material. The difference is that the raw materials are different and the mass content of polyethylene glycol in the powder in S3 is 3 wt%.
[0105] Example 5
[0106] This embodiment provides a powder metallurgy friction material, which is obtained by sintering the raw materials shown in Table 5:
[0107] Table 5
[0108]
[0109]
[0110] Please refer to Example 1 for the preparation process of this powder metallurgy friction material, the difference being the different raw materials.
[0111] Example 6
[0112] This embodiment provides a powder metallurgy friction material, which is obtained by sintering the raw materials shown in Table 6:
[0113] Table 6
[0114] Copper powder 60 70μm Iron powder 12 9μm graphite 10 20μm Molybdenum disulfide 5 2μm Tantalum carbide 4 30nm Zirconium dioxide 4 30nm aluminum powder 3 8μm polyethylene glycol 2 /
[0115] Please refer to Example 1 for the preparation process of this powder metallurgy friction material, the difference being the different raw materials.
[0116] Example 7
[0117] This embodiment provides a powder metallurgy friction material, which is obtained by sintering the raw materials shown in Table 7:
[0118] Table 7
[0119]
[0120]
[0121] Please refer to Example 1 for the preparation process of this powder metallurgy friction material, the difference being the different raw materials.
[0122] Comparative Example 1
[0123] This comparative example provides a powder metallurgy friction material, which is obtained by sintering the raw materials shown in Table 8:
[0124] Table 8
[0125] Copper powder 60 30nm Iron powder 12 9μm graphite 10 20μm Molybdenum disulfide 5 2μm Tantalum carbide 4 30nm Zirconium dioxide 4 30nm aluminum powder 3 8μm polyethylene glycol 2 /
[0126] Please refer to Example 1 for the preparation process of this powder metallurgy friction material, the difference being the different raw materials.
[0127] Comparative Example 2
[0128] This comparative example provides a powder metallurgy friction material, which is obtained by sintering the raw materials shown in Table 9:
[0129] Table 9
[0130]
[0131]
[0132] Please refer to Example 1 for the preparation process of this powder metallurgy friction material, the difference being the different raw materials.
[0133] Comparative Example 3
[0134] This comparative example provides a powder metallurgy friction material, which is obtained by sintering the raw materials shown in Table 10:
[0135] Table 10
[0136] Copper powder 60 65μm Iron powder 12 9μm graphite 10 20μm Molybdenum disulfide 5 2μm Tantalum carbide 4 65μm Zirconium dioxide 4 65μm aluminum powder 3 8μm polyethylene glycol 2 /
[0137] Please refer to Example 1 for the preparation process of this powder metallurgy friction material, the difference being the different raw materials.
[0138] Comparative Example 4
[0139] This comparative example provides a powder metallurgy friction material, which is obtained by sintering the raw materials shown in Table 11:
[0140] Table 11
[0141] Copper powder 64 90μm Iron powder 12 9μm graphite 10 20μm Molybdenum disulfide 5 2μm Tantalum carbide 0 / Zirconium dioxide 4 30nm aluminum powder 3 8μm polyethylene glycol 2 /
[0142] Please refer to Example 1 for the preparation process of this powder metallurgy friction material, the difference being the different raw materials.
[0143] Comparative Example 5
[0144] This comparative example provides a powder metallurgy friction material, which is obtained by sintering the raw materials shown in Table 12:
[0145] Table 12
[0146] Copper powder 60 90μm Iron powder 12 9μm graphite 10 20μm Molybdenum disulfide 5 2μm Tantalum carbide 4 30nm Zirconium dioxide 4 30nm aluminum powder 3 8μm polyethylene glycol 2 /
[0147] Please refer to Example 1 for the preparation process of this powder metallurgy friction material, except that the average particle size of the powder in S3 is 75 μm.
[0148] Performance testing
[0149] 1. The friction coefficient and dust amount of powder metallurgy friction materials were tested according to the TJ / CL307-2019 standard. The wear amount was calculated based on the weight loss of the friction material before and after wear. The results are recorded in Table 13.
[0150] 2. Test the powder metallurgy friction materials prepared according to GB / T 231.1-2018 standard. Figure 1 The hardness of the brake pads is shown in Table 13.
[0151] 3. The material density of the powder metallurgy friction material was tested according to GB / T 10421-2002 standard, and the results are recorded in Table 13.
[0152] 4. The porosity of the powder metallurgy friction material was tested according to GB / T 5163-2006 standard, and the results are recorded in Table 13.
[0153] Table 13
[0154]
[0155] As can be seen from the test results in Table 13, the powder metallurgy friction material provided in this application embodiment has the advantages of high heat fading resistance, low friction loss, stable friction coefficient, and low dust during braking. Compared with existing friction materials (dust content of 45 mg / cycle), the powder metallurgy friction material provided in this application embodiment reduces the amount of dust generated during braking by more than 60% through adjusting the composition and synergistic reinforcement of coarse copper powder with nano-tantalum carbide and nano-zirconia; through multi-level particle size compounding and low-temperature accelerated melting process, the density of the powder metallurgy friction material is greater than or equal to 5.2 g / cm³. 3 The prepared brake pads have a hardness greater than 35HB. The material has a coefficient of friction greater than or equal to 0.37 (350km / h), combining environmental friendliness with high-efficiency braking performance.
[0156] The embodiments of this application have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A powder metallurgy friction material, characterized in that, It is obtained by sintering the following raw materials, which, by mass percentage, include: Copper powder, 50wt%~60wt%, wherein the average particle size of the copper powder is 48μm~105μm; Iron powder 10wt%~15wt%; Graphite 8wt%~12wt%; Molybdenum disulfide 4wt%~6wt%; The tantalum carbide comprises 3 wt% to 5 wt%, wherein the average particle size of the tantalum carbide is in the nanometer range; wherein the average particle size of the tantalum carbide is less than or equal to 100 nm. Zirconium dioxide 3wt%~5wt%, wherein the average particle size of the zirconium dioxide is in the nanometer range; the average particle size of the zirconium dioxide is less than or equal to 100 nm; Aluminum powder 2wt%~4wt%; and Polyethylene glycol 1wt%~3wt%.
2. The powder metallurgy friction material according to claim 1, characterized in that, The copper powder includes at least one of electrolytic copper powder and atomized copper powder; and / or, The iron powder includes foamed iron powder; and / or, The iron powder has an average particle size of 5 μm to 10 μm; and / or, The graphite is in the form of flakes; and / or, The average particle size of the graphite is 10 μm to 50 μm; and / or, The molybdenum disulfide has an average particle size of 1 μm to 3 μm. And / or, The aluminum powder has an average particle size in the micrometer range; and / or, The polyethylene glycol has a relative molecular mass of 1000-1200; and / or, The density of the powder metallurgy friction material is greater than or equal to 5.2 g / cm³. 3 ; and / or, The porosity of the powder metallurgy friction material is less than or equal to 8%.
3. A method for preparing a powder metallurgy friction material, used to prepare the powder metallurgy friction material as described in claim 1 or 2, characterized in that, include: Provide materials other than polyethylene glycol in the raw materials, and mix them to obtain a premix; Ethanol and polyethylene glycol are added to the premix, and the mixture is ball-milled to obtain a slurry; in the slurry, the mass ratio of the premix to the ethanol is 1:(0.5~0.6), and the mass ratio of the premix to the polyethylene glycol is 1:(0.15~0.2); The slurry is spray-dried to obtain a powder, wherein the content of polyethylene glycol in the powder is 1wt%~3wt%. The powder is prepared into a blank; The blank is sintered to obtain the powder metallurgy friction material.
4. The method for preparing powder metallurgy friction material according to claim 3, characterized in that, The slurry also includes N-β-hydroxyethyl ethylenediamine triacetic acid, and the mass ratio of the premix to the N-β-hydroxyethyl ethylenediamine triacetic acid is 1:(0.003~0.005).
5. The method for preparing powder metallurgy friction material according to claim 3, characterized in that, The particle size of the powder is 100μm~220μm.
6. The method for preparing powder metallurgy friction material according to claim 5, characterized in that, The powder contains 40 wt% particles with a particle size of 200 μm to 220 μm, 30 wt% particles with a particle size of 140 μm to 160 μm, and 30 wt% particles with a particle size of 100 μm to 120 μm.
7. The method for preparing powder metallurgy friction material according to any one of claims 3 to 6, characterized in that, The preparation method of the powder metallurgy friction material further includes vacuum drying the premix; and / or... In the slurry obtained by ball milling, the average particle size of the solid particles is less than or equal to 20 μm; and / or, The powder is prepared into a blank by cold pressing, with a cold pressing pressure of 25MPa~30MPa and a holding time of 5s~10s; and / or, The sintering process is performed in a hydrogen atmosphere; and / or, The sintering temperature of the sintering treatment is 900℃~950℃, and the holding time is 1.5h~2.5h.
8. A brake pad, characterized in that, The friction body includes the powder metallurgy friction material as described in claim 1 or 2, or the powder metallurgy friction material prepared by the preparation method of the powder metallurgy friction material as described in any one of claims 3 to 7.
9. The brake pad according to claim 8, characterized in that, The hardness of the brake pads is greater than 35HB.
10. A hydro-generator, characterized in that, Includes the brake pads as described in claim 8 or 9.
Citation Information
Patent Citations
Powder metallurgy brake pad material, preparation method and brake pad
CN119120980A